The association between the FTO gene variant and alcohol consumption and binge and problem drinking in different gene-environment background: The HAPIEE study - Hubacek, Jaroslav A; Pikhart, Hynek; Peasey, Anne; Malyutina, Sofia; Pajak, Andrzej; Tamosiunas, Abdonas; Voevoda, Mikhail; Holmes, Michael V; Bobak, Martin (Gene, 2019)
BACKGROUND: Alcohol intake and tobacco smoking have significant negative health consequences and both are influenced by genetic predispositions. Some studies suggest that the FTO gene is associated with alcohol consumption. We investigated whether a tagging variant (rs17817449) within the FTO gene is associated with alcohol intake, problem drinking and smoking behaviour. METHODS: We analysed data from 26,792 Caucasian adults (47.2% of males; mean age 58.9 (±7.3) years), examined through the prospective cohort HAPIEE study. The primary outcomes were daily alcohol consumption, binge drinking, problem drinking (CAGE score 2+) and smoking status in relation to tagging variants within the FTO and ADH1B genes. RESULTS: We found no significant association of the FTO polymorphism with smoking status in either sex. The associations of the FTO polymorphism with drinking pattern were inconsistent and differed by gender. In men, GG homozygote carriers had lower odds of problem drinking (OR 0.85, 95% CI 0.75-0.96, p = 0.03). In women, the combination of the FTO/ADH1B GG/+A genotypes doubled the risk of binge drinking (OR 2.10, 95% CI 1.19-3.71, p < 0.05), and the risk was further increased among smoking women (OR 4.10, 95% CI 1.64-10.24, p = 0.008). CONCLUSIONS: In this large population study, the FTO gene appeared associated with binge and problem drinking, and the associations were modified by sex, smoking status and the ADH1B polymorphism.
Keywords: genetické asociační studie; senioři; nárazové pití alkoholu; alkoholdehydrogenasa; Aged; Male; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; gen pro FTO; lidé; Genotype; lidé středního věku; Humans; běloši; sexuální faktory; Smoking; Sex; Polymorphism, Single Nucleotide; Middle Aged; Sex Factors; alkoholismus; Alcohol intake; Gene-Environment Interaction; Alcoholism; jednonukleotidový polymorfismus; pití alkoholu; White People; Binge Drinking; mužské pohlaví; Alcohol Dehydrogenase; Genetic Association Studies; prospektivní studie; Binge drinking; ženské pohlaví; genotyp; FTO; Alcohol Drinking; Female; ADH1B; interakce genů a prostředí; Polymorphism; kouření; Prospective Studies